2021
DOI: 10.1111/ajo.13434
|View full text |Cite
|
Sign up to set email alerts
|

The myometrial‐cervical ratio (MCR): Assessing the diagnostic accuracy of a novel ultrasound measurement in the diagnosis of adenomyosis

Abstract: Background:Adenomyosis is histologically defined by the presence of endometrial glands and stroma in the myometrium. To date, there are no standardised ultrasound findings that reliably predict histological adenomyosis.Aims: This study aimed to determine the diagnostic accuracy of a novel sonographic measurement for adenomyosis, the myometrial-cervical ratio (MCR), when compared with histopathological diagnosis. Materials and Methods:A single-centre retrospective study was performed. The MCR was calculated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 17 publications
2
15
2
Order By: Relevance
“…The optimal MCR cut‐point in this subgroup was 1.79, which achieved 55.6% sensitivity and 62.8% specificity, with 58.5% of samples correctly classified (Table 2). Using the previously described cut‐point of 1.74 13 59.0% sensitivity, 59.0% specificity, and 59.0% correct classification were achieved. There was no statistical evidence of a difference in the AUROC using either cut‐point ( P = 0.88).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The optimal MCR cut‐point in this subgroup was 1.79, which achieved 55.6% sensitivity and 62.8% specificity, with 58.5% of samples correctly classified (Table 2). Using the previously described cut‐point of 1.74 13 59.0% sensitivity, 59.0% specificity, and 59.0% correct classification were achieved. There was no statistical evidence of a difference in the AUROC using either cut‐point ( P = 0.88).…”
Section: Resultsmentioning
confidence: 99%
“…Mooney et al showed an association between MCR and histological diagnosis of adenomyosis when samples with fibroids in the MCR measurement were excluded 13 . Using an MCR cut‐point of 1.74 achieved a sensitivity of 67.2% and specificity of 66.2%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations